Geomorphologic basis and national practice of creek restoration - Báthoryné Nagy, Ildikó Réka; Novák, Tibor József (4D Journal of Landscape Architecture and Garden Art, 2006)
Bank and waterside regulation has modified the hydraulic condition of the watercour.se and has basically transformed its ecological and land use character. Negative effects caused by the modification were becoming pressing to change water management tools. At the same time new criteria were introduced to water management planning such as ecological connectivity. preserving riverine ecosystem, restoring water quality and sinking ground water level and reorganizing joint land use.